2017
DOI: 10.1103/physrevd.96.043011
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-ray puzzle in Cygnus X: Implications for high-energy neutrinos

Abstract: The Cygnus X region contains giant molecular cloud complexes and populous associates of massive young stars. The discovery of spatially extended, hard γ-ray emission in Cygnus X by both Milagro and Fermi indicates that Cygnus X is also a potential source of high-energy Galactic neutrinos. Here, we adapt our single-zone model for cosmic ray interactions in the central molecular zones of starburst galaxies for use in Cygnus X. We calculate the potential neutrino flux corresponding to the hard γ-ray emission from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
(107 reference statements)
0
17
0
Order By: Relevance
“…High-energy neutrinos produced by inelastic nuclei collisions in the Cygnus X region may have a large enough flux to be detected with the IceCube Observatory, as estimated by Yoast-Hull et al (2017) using a single-zone model of CR interactions with the molecular gas. The planned observations of the Cygnus region with the high sensitivity and good angular resolution Cherenkov Telescope Array have the potential to provide imaging and spectra of the region between a few tens of GeV up to ∼ 100 TeV (Weinstein et al 2015).…”
Section: Cosmic Rays In Superbubblesmentioning
confidence: 99%
“…High-energy neutrinos produced by inelastic nuclei collisions in the Cygnus X region may have a large enough flux to be detected with the IceCube Observatory, as estimated by Yoast-Hull et al (2017) using a single-zone model of CR interactions with the molecular gas. The planned observations of the Cygnus region with the high sensitivity and good angular resolution Cherenkov Telescope Array have the potential to provide imaging and spectra of the region between a few tens of GeV up to ∼ 100 TeV (Weinstein et al 2015).…”
Section: Cosmic Rays In Superbubblesmentioning
confidence: 99%
“…The influence of the models is evident as Tova et al [36] suggest a neutrino spectrum from Cygnus X which is most likely not detectable, whereas the model from this work coincides with the limit of IceCube. Additionally, in Figure 8…”
Section: Cosmic Raysmentioning
confidence: 52%
“…Secondary particle interactions can produce observable emissions not only in interacting galaxy systems but also in star-forming and/or starburst galaxies, where supernovae can accelerate high-energy CRs and trigger subsequent particle interactions. Previous studies incorporating π 0 decays, bremsstrahlung, inverse Compton and synchrotron emissions have shown that CR interactions can be used to explain the gamma-ray observations of the starburst galaxy M82 (Yoast-Hull et al 2013), the Cygnus X region (Yoast-Hull et al 2017b) and the ultra-luminous infrared galaxy Arp 220 (Yoast-Hull et al 2017a). Interestingly, for Arp 220 we can estimate the CR luminosity density from a galaxy merger scenario in the central molecular zone as L cr,merger 1 2 p M g v 2 s R vs −1 ≈ 9.87 × 10 43 vs 500km s −1 3 erg s −1 , using the gas mass M g = 6 × 10 8 M (Sakamoto et al 2008) and R = 70 pc (Downes & Eckart 2007), which is roughly twice as much as the best-fitting supernova CR luminosity Yoast-Hull et al (2015), L cr,SNe E cr,SN R SN ≈ 4.76 × 10 43 erg s −1 , for a typical CR energy injected by supernovae of E cr,SN ≈ 10 50 erg and a supernova rate R SN ≈ 15 yr −1 .…”
Section: Summary and Discussionmentioning
confidence: 99%